The Role of Notaries in Commodity Futures Trading from the Perspective of Islamic Economic Law at Pt Equityworld Futures Semarang - Zunitasari, Zunitasari (Master of Notarial Law, Faculty of Law, Sultan Agung Islamic University, 2025)
Background: Commodity futures trading is one of the important instruments in the financial market that provides hedging opportunities and speculation on future commodity prices. In Indonesia, this activity is regulated and supervised by the Commodity Futures Trading Supervisory Agency (BAPPEBTI) and is carried out through futures exchanges such as the Jakarta Futures Exchange (JFX) or the Indonesia Commodity and Derivative Exchange (ICDX). In this transaction, the validity and legal force of the contract are very important to avoid disputes and ensure legal certainty for the parties. This is where the role of a notary becomes significant as a public official who validates the deeds of agreement and guarantees their formal validity. However, in the legal context, futures trading activities are often questioned as halal because they are feared to contain elements of gharar (uncertainty), masyir (gambling), and excessive speculation. Therefore, it is important to examine how the role of notaries in this futures trading can be aligned with the principles of Islamic economic law. Research Objectives: - to analyze the role of notaries in the creation and legalization of commodity futures trading contracts on futures exchanges. -assess the conformity of commodity futures trading practices with the principles of Islamic economic law. -explains how notaries can help maintain the validity of contracts so that they do not conflict with sharia principles, and become part of a legal system that guarantees justice and transparency in economic activities. The research method uses a normative legal research method, namely research that focuses on the analysis of legal norms.